Treatment strategy for laparoscopic hiatal hernia repair. Issue 4 (20th January 2021) - Yano, Fumiaki; Tsuboi, Kazuto; Omura, Nobuo; Hoshino, Masato; Yamamoto, Se R.; Akimoto, Shunsuke; Masuda, Takahiro; Mitsumori, Norio; Ikegami, Toru
Abstract: Introduction: According to the anatomy‐function‐pathology classification, the recurrence rates of A2 and A3 hiatal hernia (HH) after laparoscopic fundoplication are higher than the rate of A1 HH. Therefore, we introduced mesh reinforcement for A2 and A3 cases. In addition, gastropexy was added to A3 cases. We present the strategy for HH repair. Methods: In all, 537 patients (mean age 55.4 ± 16.7 years, 219 women) who underwent primary laparoscopic fundoplication for HH from January 1995 to October 2019 were included. They were divided into three groups by A factor (A1:A2:A3 = 296:156:85). Their clinical data were collected in a prospective fashion and retrospectively reviewed. Results: The median age (years) of the patients in each group was A1:A2:A3 = 46:63:74 years, and age was directly proportional to the size of HH ( P  < 0.0001). The proportion of females was significantly higher in A3 than in other classes ( P  < 0.0001). Preoperative reflux esophagitis was severe in A2 ( P  < 0.0001) and operation time (min) was directly proportional to HH size (A1:A2:A3 = 135:167:193, P  < 0.0001). The recurrence rate of conventional laparoscopic fundoplication was 15% (46/304), and it was higher for A2 and A3 than for A1 ( P  = 0.027). However, with reinforcement of the hiatus using a mesh and gastropexy, the recurrence rates decreased. Conclusion: Combining mesh reinforcement and gastropexy may reduce the recurrence rate of para‐ and mixed‐type HH.